Utilization of Mobile-Based Learning Media to Improve Education Accessibility in Remote Areas - Ahmad Robith Firdausi (PT. Anagata Sembagi Education, 2025)
Inequality in access to education between urban and remote areas is still a serious problem in the education system in Indonesia. Many students in remote areas face obstacles in obtaining proper education, mainly due to the limited number of educators, lack of educational facilities, and difficult access to transportation. Along with the rapid development of information and communication technology, mobile-based learning media emerged as a potential solution to overcome these obstacles. This study aims to examine the utilization of mobile-based learning media in improving accessibility and quality of education in remote areas. The method used is a qualitative study with a case study approach in several primary and secondary schools in remote areas in Indonesia. The results show that the use of mobile media such as educational applications, learning videos, and Android-based e-learning platforms can expand the range of learning, increase student participation, and allow teaching and learning activities to take place flexibly without relying on the physical presence of teachers. In addition, students show increased motivation to learn and independence in completing tasks. However, the implementation of this media still faces several challenges, including limited internet network, lack of mobile devices, and low digital literacy of teachers and students. Support from various parties, both government and private, is needed to provide infrastructure, training and development of appropriate learning content. With the right approach, mobile-based learning media has the potential to be a strategic tool in expanding access to inclusive and equitable education throughout Indonesia.